2005
DOI: 10.1152/ajpheart.00484.2004
|View full text |Cite
|
Sign up to set email alerts
|

Meal-related increases in vascular reactivity are impaired in older and diabetic adults: insights into roles of aging and insulin in vascular flow

Abstract: A fatty meal induces vasodilatation (of both resting and stimulated forearm flow) in healthy young adults, an effect most likely mediated by the vasodilator actions of insulin. We therefore hypothesized that an impaired meal-related vascular response might be an in vivo marker of vascular insulin resistance, related to the presence of diabetes and/or higher age. Postprandial vascular responses were assessed in three groups of subjects: 15 Type 2 diabetic subjects (age 58 +/- 8 yr), 15 age-, gender-, and body m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
39
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 42 publications
5
39
0
1
Order By: Relevance
“…Here we have again shown that age-related decrements in LBF are associated with impairments in muscle MBV responses to feeding, findings that are consistent with reports of decrements in fed-state forearm MBF (inferred from indirect measurements) (Skilton et al 2005) and also the absence of increased muscle MBF in older people fed EAA and sucrose (Timmerman et al 2012). Whereas it is well established that acute bouts of exercise enhance microvascular perfusion in both human (Vincent et al 2006) and rodent muscle (Sjøberg et al 2011), the effects of an acute neutraceutical intervention (in this case cocoa flavanols) on muscle MBF in response to nutrition, have until now remained poorly defined.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Here we have again shown that age-related decrements in LBF are associated with impairments in muscle MBV responses to feeding, findings that are consistent with reports of decrements in fed-state forearm MBF (inferred from indirect measurements) (Skilton et al 2005) and also the absence of increased muscle MBF in older people fed EAA and sucrose (Timmerman et al 2012). Whereas it is well established that acute bouts of exercise enhance microvascular perfusion in both human (Vincent et al 2006) and rodent muscle (Sjøberg et al 2011), the effects of an acute neutraceutical intervention (in this case cocoa flavanols) on muscle MBF in response to nutrition, have until now remained poorly defined.…”
Section: Discussionsupporting
confidence: 91%
“…For example, decreased arterial compliance in older age leads to hypertension and coronary artery disease (DeSouza et al 2002;Dinenno et al 1999;Lind & Lithell 1993). In addition, when compared to younger individuals, older individuals exhibit 20-30% reductions in limb conduit artery blood flow under both postabsorptive (Donato et al 2006) and postprandial conditions (Skilton et al 2005), due to both a decrease in capillary number (Coggan et al 1992) and increased sensitivity to vasoconstrictors such as alpha-adrenergic innervation (Barrett-O'Keefe et al 2013). Such blunted blood flow responses may contribute to age-related declines in anabolic responses to feeding (Durham et al 2010), by reducing delivery and/or utility of insulin and amino acids (AA) in muscle (Clark et al 2003;Timmerman et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the optimal nutritive network consists of tortuous capillaries contacting myocytes, the nonnutritive network supplies muscle connective tissue and adipocytes and has minimal myocyte contact (33,45). Whereas feeding has been shown to stimulate both limb (i.e., femoral and brachial) (26,28,34) and muscle nutritive (30,33) blood flow, relationships between muscle AA utilization and blood flow remain poorly defined. Nonetheless, evidence is mounting that recruitment of muscle microvasculature is important in maintaining protein (40) and carbohydrate (CHO) (42,43) …”
mentioning
confidence: 99%
“…Intriguingly, declines in peripheral blood flow with ageing are not restricted to postabsorptive periods but are also observed when subjects are challenged with vasodilatory stimuli, such as food intake (31) and exercise (13,25). For example, characteristic increases in limb (forearm brachial) blood flow in the postprandial period are impaired in both older and diabetic adults (31), with age rather than diabetes being the principal determinant.…”
mentioning
confidence: 99%